Penyelesaian Tindak Pidana yang di Lakukan Anak Secara Diversi dalam Persfektif Hukum Pidana Islam - Dewi Nirmala; Ema Fathimah (CV. Doki Course and Training, 2025)
This study examines acts of violence in educational settings, including cases that occurred in Sungai Semut Village, Makarti Jaya District, Banyuasin Regency. The objective of the study was to determine the peace process through diversion in cases of violence perpetrated by children and to examine its resolution from the perspective of Islamic criminal law. The method used was empirical juridical with a qualitative approach through interviews and descriptive analysis. The results showed that diversion is an alternative legal resolution that emphasizes responsibility, behavioral improvement, and the involvement of families and victims without going through the courts. Diversion aligns with the principles of islah and shura in Islamic law, which emphasize peace, restoration of social relations, and opportunities for children to improve themselves. Thus, diversion reflects the values ​​of justice, compassion, and the common good as emphasized in Islamic teachings. The implications of this study indicate that diversion is not merely a legal mechanism, but also a means of child development and social recovery. Therefore, the implementation of diversion needs to be strengthened through support from the government, supporting institutions, and the community to achieve peaceful, just conflict resolution in accordance with national and Islamic legal values.